Sound worlds of Japanese gardens : an interdisciplinary approach to spatial thinking - Fowler, Michael D. (Cultural and media studies., 2014)
Michael D. Fowler presents an interdisciplinary approach to investigating the sound world of traditional Japanese gardens by drawing from the diverse fields of semiotics, acoustic ecology, philosophy, mathematical modelling, architecture, music, landscape theory and acoustic analysis. Using projects - ranging from data-visualisations, immersive sound installations, algorithmically generated meta-gardens and proto-architectural form finding missions - as creative paradigms, the book offers a new framework for artistic inquiry in which the sole objective is the generation of new knowledge through the act of spatial thinking.